Test of speaking in the school-based assessment in an upper secondary school - Saehu, Andang (International Journal of English Language and Pedagogy, 2024)
Speaking is one of language skills taught but not tested in the national examination. It is fully to be prepared and administered by the schools in the school examination. However, the government and public did not have any data-based information about how the test of speaking was developed and administered. The current study investigates the ways the English teachers developed and administered the speaking test in the school-based assessment (SBA) in one of the private upper secondary levels of education in Garut, West Java. The selection of the school was done purposively with considering that the school is accessible by the researcher and A recognition for national accreditation. The result shows that the English teachers had different ways of developing and administering the speaking test. This study suggests that the government needs to design the national-based test specification developed by the experts in order to be used to measure whether the students have attained the competence standards for graduation.